Prevalence and genetic diversity of porcine reproduction and respiration syndrome viruses in Sichuan Province from 2023–2024 - MingXiang Li; MingXiang Li; Min Wang; Hao Li; KeLei Zhou; ZhiQiang Hu; ZhiQiang Hu; WenXing Bai; GuiYing Hao; GuiYing Hao; GuangWen Yan; GuangWen Yan (Frontiers in Veterinary Science)
IntroductionPorcine reproductive and respiratory syndrome (PRRS), caused by porcine reproductive and respiratory syndrome virus (PRRSV), occurs frequently in China, and severely hinders the healthy development of the pig farming industry.MethodsTo determine the genetic diversity and epidemiological characteristics of PRRSV strains in Sichuan Province, we collected 499 clinical samples suspected of PRRSV infection from 101 pig farms in 19 cities from 2023 to 2024.Results and DiscussionAmong the 499 samples, 162 were positive for PRRSV, with a total prevalence of 32.46% according to RT-qPCR. Among the 101 pig farms, 55 were positive farm, resulting in a rate of 54.46%. Further analysis of the complete ORF5 gene sequences of 56 PRRSV strains revealed that they could be classified into six lineages: PRRSV-1, lineage 8 (HP-PRRSV), lineage 5 (Classical PRRSV), lineage 1.8 (NADC30-like strain), lineage 1.5 (NADC34-like strain), and lineage 3.5 (QYYZ-like strain). Notably, both the lineage 8 and PRRSV-1 strain were detected in the same sample, indicating the presence of mixed infection. This study revealed the coexistence of multiple lineages of PRRSV in Sichuan Province, with the lineage 1.8 emerging as the predominant epidemic lineage. The concurrent prevalence of multiple lineages underscores the importance of selecting matching vaccines on the basis of locally prevalent strains and the need for continuous epidemiological monitoring of PRRSV.